Agonism and performance in adolescent football players in informal physical education settings - Sara Aliberti; Francesca D’Elia; Giuseppe Giardullo; Giuseppe Giardullo; Gaetano Raiola (Frontiers in Sports and Active Living)
Football is one of the most widely practiced sports in the world, and competition significantly influences athletic performance, especially in adolescents who experience emotional pressure that impacts their performance through the management of performance-related stress. Physical education is integrated within the school curriculum, but it is also typically delivered in sports associations engaged in competitive activities, which become informal learning environments as they pursue the same educational goals as schools. However, few studies have focused on this aspect, particularly the role of emotions and their relationship with performance anxiety in adolescent football players. The aim of this study was to analyze the relationship between pre-competitive anxiety and emotional regulation in adolescents regarding competitive performance. The study design was exploratory. A sample of 79 Under-19 football players, with a mean age of 14.6 (±1.89) years, was recruited through convenience sampling. A battery of pre-competition questionnaires was administered, including the Sport Anxiety Scale-2 (SAS-2) to measure anxiety levels and the Trait Emotional Intelligence Questionnaire (TEIQue-SF) to assess pre-competition emotional levels. Spearman's correlation was used to evaluate the strength and direction of the relationship between emotional levels and anxiety, while Chi-square test was employed to examine differences in anxiety levels across different player roles. The results showed that 70% of the football players displayed normal anxiety levels, with no significant differences across player positions. No significant correlation was found between emotional levels and anxiety. The primary causes of anxiety were cognitive concerns and bodily sensations, which negatively affected concentration. Although emotions were generally high, they did not appear to directly influence performance anxiety, suggesting that other factors may contribute to pre-competitive emotional regulation. In conclusion, contrary to common belief, performance anxiety in adolescent football competitions does not have a direct impact on emotional levels.